Personality disorders and states of aloneness - McGraw, John G. (Value Inquiry Book Series, 2012)
This book is the second volume of an interdisciplinary study, chiefly one of philosophy and psychology, which concerns personality, especially the abnormal in terms of states of aloneness, primarily that of the negative emotional isolation customarily known as loneliness. Other states of aloneness investigated include solitude, reclusiveness, seclusion, desolation, isolation, and what the author terms "aloneliness," "alonism," "lonism," and "lonerism." Insofar as this study most explicitly focuses on abnormal personalities, it employs the general and specific definitions of personality aberrations as formulated by the American Psychiatric Association in its latest edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) . The author views personality as preeminently comprised of the individual's interpersonal relationships. Unlike the DSM-IV , he proposes that people with personality disorders not only possibly but necessarily manifest deviancy regarding interpersonal functioning via serious shortcomings in shared inwardness, paramountly reciprocated intimacy. This work also engages in an analysis of five social factors that are conducive to predisposing, precipitating, and maintaining negative kinds of personality and aloneness. The author has formed these factors into an acronym titled SCRAM since when they are present, intimacy scurries away and in its absence, loneliness and other sorts of unwanted aloneness scamper in and fill the person with unhappiness via, for instance, sadness and self-worthlessness. The constituents of SCRAM are the following social illnesses: S uccessitis (for example, the fixation on fame and fortune), C apitalitis (greed-driven, unfettered capitalism), R ivalitis (competitivitis), A tomitis (hyper-individualism), and M aterialitis (for example, the anti-spirituality of consumeritis). In sum, this book provides a different perspective on personality via the lenses of various types of aloneness and their lack of public and private intimacy, especially love.